POTENTIAL AND PROSPECTUS IN AGRICULTURAL DEVELOPMENT OF LAI CHAU PROVINCE, VIETNAM - Nguyen Thu Thuy; Duong Thi Tinh; Nguyen Quang Hop (International Journal of Business and Social Science Research, 2021)
Lai Chau province has many potentialities in agricultural development such as climate, soil, diverse topography, support policies of the Government, locality, long tradition of farming...Period 2016 - 2020, the growth rate of the agricultural sector will maintain from 5-6%, the food production is increased, Some dominant crops of the province are being invested for development: tea, medicinal plants, specialty rice...However, the level of deep processing for agricultural products is still low, so the value of goods is not high, the products are mainly consumed in the domestic market, the penetration into supermarkets or export is still limited...Therefore, building a suitable agricultural development orientation will help farmers, businesses, and the Lai Chau province government to have specific solutions in the future to bring high-tech agriculture becomes a key economic direction of the province.